The Polemic of Veil Restriction at UIN Sunan Kalijaga (Identity, Discourse Contest, and Struggle for Authority) - Humaidi, Zuhri; Najib, Agus Moh.; Muzammil, Shofiyullah (FIKRAH, 2022)
The regulation of veil restriction at UIN Sunan Kalijaga, and its ensuing controversy, is a significant and meaningful event. The symbolic significance of the veil reflects identity problems, power dynamics, and disparities in religious, social, and political perspectives. This article analyses the ongoing power relations and practices underlying narrative discourse by collecting data in the mass media from February to April 2018. Using discourse analysis and Michel Foucault's Genealogy theory, the data was analyzed. The result shows; first, the case of the veil restriction at UIN Jogja is massive and phenomenal that it reflects the context of PTKI and even contemporary Indonesian Islam. Second, the cadres’ debate is replete with discourse contestation between opposing ideological factions, demonstrating the tight connection between knowledge and power. Third, it demonstrates the increasingly diversified form of contemporary Islam in Indonesia. Finally, this article helps to understand the dynamics of current Islamic thought, notably in PTKI, and the challenges of democracy in Indonesia.